The Effect of Using Wipe Clean Flash Cards on the Ability to Construct Simple Mandarin Sentences among Grade XI-10 Students at SMA Negeri 1 Lamongan - Mila Budi Februani; Mintowati Mintowati; Plernpit Propungsri (Universitas Negeri Surabaya, 2025)
Learning media serve as tools to convey messages (learning material) in teaching and learning activities. Without the use of instructional media, the learning environment becomes monotonous, leading to a lack of focus and student interest in the material presented. This, in turn, affects student learning outcomes. This study was motivated by several problem findings, including frequent errors in constructing simple Mandarin sentences, lack of student attention during lessons, and low interest in Mandarin subjects. The aim of this study is to examine the effect of using wipe clean flash cards on students' ability to construct simple Mandarin sentences. This research is a pre-experimental study with a quantitative approach using a one-group pretest-posttest design. The sample consisted of the entire population of class XI-10, with 18 female and 20 male students at SMA Negeri 1 Lamongan. The independent variables were the use of wipe clean flash cards and teaching implementation. The dependent variable was the ability to construct simple Mandarin sentences. Data were collected through observation, tests, and student response questionnaires. Instruments included observation sheets, test questions, and response questionnaires. Data were analysed using statistical techniques. The results showed a significant effect, with the average pretest score at 51.2 and posttest at 78.8. A t-test revealed a calculated t-value of 8.97, which exceeded the critical value of 1.69 at the 5% significance level (α = 0.05; df = 37), indicating that H₀ is rejected and Hₐ is accepted. It can be concluded that the use of wipe clean flash cards significantly affects the ability to construct simple Mandarin sentences.